A study on the efficacy of natural language generation techniques for similar writing personalities - Anwar, Ahmed; Tanzir, Hasan Mohammod; Hosain, Abdul Halim; Islam, Taslima; Raya, Nusrat Zaman (Brac University, 2024)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Computer Science, 2024.